2020
DOI: 10.1088/1475-7516/2020/01/017
|View full text |Cite
|
Sign up to set email alerts
|

Probing a stationary non-Gaussian background of stochastic gravitational waves with pulsar timing arrays

Abstract: We introduce the concept of stationary graviton non-Gaussianity (nG), an observable that can be probed in terms of 3-point correlation functions of a stochastic gravitational wave (GW) background. When evaluated in momentum space, stationary nG corresponds to folded bispectra of graviton nG. We determine 3-point overlap functions for testing stationary nG with pulsar timing array GW experiments, and we obtain the corresponding optimal signal-tonoise ratio. For the first time, we consider 3-point overlap functi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 50 publications
(135 reference statements)
1
25
0
Order By: Relevance
“…The characterization of the non-Gaussian properties of the SGWB is a potential tool to discriminate whether a SGWB has a primordial or astrophysical origin. The primoridal 3-point function of the GW field, hh 3 i, is unobservable, due to the decoherence of the associated phase (because of the propagation, and the finite duration of the measurement [23,24]), with, possibly, the exception of very specific shapes [30,39]. It is more convenient to consider the non-Gaussianity associated with the GW energy density angular distribution, which is not affected by this problem [25].…”
Section: B Angular Bispectrum Of Gw Energy Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…The characterization of the non-Gaussian properties of the SGWB is a potential tool to discriminate whether a SGWB has a primordial or astrophysical origin. The primoridal 3-point function of the GW field, hh 3 i, is unobservable, due to the decoherence of the associated phase (because of the propagation, and the finite duration of the measurement [23,24]), with, possibly, the exception of very specific shapes [30,39]. It is more convenient to consider the non-Gaussianity associated with the GW energy density angular distribution, which is not affected by this problem [25].…”
Section: B Angular Bispectrum Of Gw Energy Densitymentioning
confidence: 99%
“…In light of this fact, a measurement of non-Gaussianity would be a signal of large scale coherency, that would likely point to a cosmological origin of the signal. Previous works showed that inflation can result in a sizeable and nonvanishing 3-point function hh 3 i for the graviton wave function, but that this is generically nonobservable in interferometers [23,24], due to the decoherence of the phase the GW wave-function h induced by the GW propagation, and due to the finite duration of the measurement (see [30] for a possible exception to this conclusion, occurring for a very specific shape of the bispectrum). Since the phase does not affect the GW energy density, we argue that the energy density is a much better variable to study the statistics of the SGWB.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of measuring pulsar X-ray emission, NASA's Station Explorer for X-ray Timing and Navigation Technology (SEXTANT) mission, involved demonstrating real-time on-board X-ray Pulsar Navigation [7]. In astrophysics, a Pulsar Timing Array (PTA) was designed to detect and analyze variations in the arrival times of pulsar generated signals which may be caused by gravitational waves [8]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…6 An example of a slow-roll potential. Acceleration occurs when the potential energy of the field, V (φ), dominates over the kinetic energy term 1 2φ 2 . Inflation ends at φ end when the kinetic energy increases to be approximately equal to the potential term, 1 2φ 2 ≈ V .…”
Section: Statementmentioning
confidence: 99%
“…4. 2 The structure of the 3-point function in eq (4.2.14) requires that the three GWs entering in the correlator originate from a common directionn in the sky. In the graphical representation above, we show with the red spot the common region of emission of three GWs (which can be of cosmological origin); with the blue blob the region containing GW detectors (which can be of astrophysical size, as in the case of PTA experiments).…”
Section: List Of Figuresmentioning
confidence: 99%